2008
DOI: 10.1111/j.1601-5223.1992.tb00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosystematic research in Aegilops and Triticum

Abstract: As Kihara had only 1 to 3 accessions of each diploid analyzer species in his germplasm collection, we conclude the genome formulae for Aegilops and Triticum published by him between 1920 and 1960 were largely based on the typological concept applied to cytogenetic research. The same restriction applies to his concept of “modified genomes” in the tetraploid Aegilops species, which therefore may not actually be modified. Genome analysis by itself is not a very fine‐tuned experimental technique. A biological spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…In agreement with the first hypothesis, Pseudoroegneria and Hordeum hybridized and were at the origin of the species-rich allotetraploid genus Elymus [23,30]. If recent interspecific introgression were responsible for the incongruence pattern we observed it would likely proceed via polyploids because all genera investigated here are currently intersterile [71-74]. Polyploids could serve as bridges of genes between diploid species [22].…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with the first hypothesis, Pseudoroegneria and Hordeum hybridized and were at the origin of the species-rich allotetraploid genus Elymus [23,30]. If recent interspecific introgression were responsible for the incongruence pattern we observed it would likely proceed via polyploids because all genera investigated here are currently intersterile [71-74]. Polyploids could serve as bridges of genes between diploid species [22].…”
Section: Discussionsupporting
confidence: 87%
“…This concurs with observations of some molecular studies since the study of biochemical characters for high molecular weight glutinen subunits in T. monococcum revealed that these characters are quite different from their parallels in T. urartu (Ciaffi et al 1998). This reflects the reproductive isolation of the two species and agrees with their bioclassification treatment and the new naming which consider T. urartu a separate species from T. monococcum (Waines and Barnhart 1992;Morrison 1993). This, in turns, interprets the separation of the two species in the tree based on protein analysis.…”
Section: Genetic Relationships Among Triticum Speciessupporting
confidence: 67%
“…However, several studies indicated that the B genome of wheat has significantly diverged from all potential extant wild progenitors, although it is closer to A. speltoides than to any of the other Sitopsis genomes3536. Hence, the majority of evidence seems to suggest that A. speltoides is the most likely living relatives of B genomes donor species910.…”
Section: Resultsmentioning
confidence: 99%